2018
DOI: 10.3390/ijns4020020
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefit of Selective CMV Testing after Failed Newborn Hearing Screening

Abstract: Evidence-based guidelines for the prevention, diagnosis and treatment of congenital cytomegalovirus (cCMV) were recently released by two independent expert groups. Of particular emphasis was the relationship between cCMV and sensorineural hearing loss (SNHL), a major component of the virus’ overall disease burden. In this study, a literature review was performed to estimate the proportion of cCMV-related SNHL cases, which might be identified through selective cCMV testing following failed newborn hearing scree… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…It may be reasonable to suggest testing for cCMV infection in infants with unexplained intrauterine growth retardation at birth or prematurity [28]. Targeted CMV testing among newborns who failed newborn hearing screening, has been explored by different study groups [29,30]. The study by Fowler et al [29] evaluated a group of newborns specifically screened for CMV, who underwent newborn hearing screening in the follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be reasonable to suggest testing for cCMV infection in infants with unexplained intrauterine growth retardation at birth or prematurity [28]. Targeted CMV testing among newborns who failed newborn hearing screening, has been explored by different study groups [29,30]. The study by Fowler et al [29] evaluated a group of newborns specifically screened for CMV, who underwent newborn hearing screening in the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Access to the data used in this study can only be provided to external parties under the conditions of the cooperation contract of this research project and can be assessed upon request, after written approval at InGef GmbH (Tel. +49 (30) 21 23 36-471; info@ingef.de), if required.…”
Section: Introductionmentioning
confidence: 99%
“…Some, however, would test for cCMV infection if SSD was suspected but not for UHI. Given that cCMV infection is associated with any degree of HI [ 57 ], it is recommended that all children who fail the screening are screened for cCMV [ 58 ]. Thus, this should apply to children with any degree of UHI and those with SSD.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis is important for considering drug treatment with ganciclovir or valganciclovir, given that several studies have shown their usefulness for improving hearing loss or preventing its progression in these children. For a congenital diagnosis it is necessary to have a positive PCR test in urine before 21 postnatal days and that is the reason for doing retest in hearing screening before this date [30][31][32].…”
Section: Additional Remarksmentioning
confidence: 99%